Lamb problem for a half-space covered with a two-axially prestretched layer - Emiroglu, I; Tasci, F; Akbarov, SD (SPRINGER, 2004)
Within the framework of a piecewise homogeneous body model, with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies, an approach for investigating the Lamb problem for a half-space covered with a layer is developed. It is assumed that the half-space and the cover layer have two-axial initial stresses operating parallel to the layer plane. To the free face of the layer, a normal point force changing harmonically with time is applied. For solving the corresponding boundary value problems, the double-exponential Fourier transformation is employed. An algorithm for obtaining numerical results is proposed, which is examined in particular cases. Numerical results for the influence of prestretching the cover layer on the interfacial stresses are presented.
Keywords: prestretching; Lamb problem; two-axial initial stresses; cover layer; half-space; Mechanics; Materials Science; Polymer Science